Atypical Blepharospasm with Oromandibular Dystonia Associated with Cerebral Amyloid Angiopathy. (4th May 2022) - Carey, Andrew R.; Miller, Neil R.
ABSTRACT: A case of atypical blepharospasm with oromandibular dystonia is presented in a patient found to have cerebral amyloid angiopathy on magnetic resonance imaging and a shared mechanism is discussed.